Clinical development of triple-combination CFTR modulators for cystic fibrosis patients with one or two F508del alleles. Issue 2 (17th June 2019) - Taylor-Cousar, Jennifer L.; Mall, Marcus A.; Ramsey, Bonnie W.; McKone, Edward F.; Tullis, Elizabeth; Marigowda, Gautham; McKee, Charlotte M.; Waltz, David; Moskowitz, Samuel M.; Savage, Jessica; Xuan, Fengjuan; Rowe, Steven M.
Cystic fibrosis (CF) is caused by mutations in the CF transmembrane conductance regulator gene ( CFTR ) that result in diminished quantity and/or function of the CFTR anion channel. F508del-CFTR, the most common CF-causing mutation (found in ∼90% of patients), causes severe processing and trafficking defects, resulting in decreased CFTR quantity and function. CFTR modulators are medications that increase the amount of mature CFTR protein (correctors) or enhance channel function (potentiators) at the cell surface. Combinations of CFTR correctors and potentiators ( i.e. lumacaftor/ivacaftor, tezacaftor/ivacaftor) have demonstrated clinical benefit in subsets of patients. However, none are approved for patients with CF heterozygous for F508del -CFTR and a minimal function mutation, i.e. a mutation that produces either no protein or protein that is unresponsive to currently approved CFTR modulators. Next-generation CFTR correctors VX-659 and VX-445, each in triple combination with tezacaftor and ivacaftor, improve CFTR processing, trafficking and function in vitro and have demonstrated clinical improvements in phase 2 studies in patients with CF with one or two F508del - CFTR alleles. Here, we present the rationale and design of four randomised phase 3 studies, and their open-label extensions, evaluating VX-659 (ECLIPSE) or VX-445 (AURORA) plus tezacaftor and ivacaftor in patients with one or two F508del - CFTR alleles. An efficient development programme for VX-659 and VX-445 in triple combination with tezacaftor/ivacaftor in patients with CF with one or two F508del - CFTR alleles was designed based on extensive CFTR modulator experience and pre-clinical and clinical data. http://bit.ly/2UBh6EV